Calling People Names:: Reading Imposture, Confession, and Testimony in and after Michael Ondaatje’s The English Patient - Dawson, Carrie (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (The University of New Brunswick, 2000)
Lacan states that although naming is ultimately an arbitrary marker of identity, it nevertheless functions as a stabilizing "guarantee" that we can agree upon identity in some way. In The English Patient, Michael Ondaatje's deferral of names in the first section, and the English patient's withholding of his identity — whether through genuine trauma or through imposture — forces readers into a partnership with the characters to adopt an alternative narrative practice in which we might forego the desire for stable identities. The related sub-theme of erasure, of nations, of history, of individual identity, is attempted through a progression of confession through to testimony, where transformative renewal might be forged. The desire, both of the characters and of the reader, for a "fully named world," needs a re-evaluation.